Time-dependent changes in the microenvironment of injured spinal cord affects the therapeutic potential of neural stem cell transplantation for spinal cord injury - Nishimura Soraya; Yasuda Akimasa; Iwai Hiroki; Takano Morito; Kobayashi Yoshiomi; Nori Satoshi; Tsuji Osahiko; Fujiyoshi Kanehiro; Ebise Hayao; Toyama Yoshiaki; Okano Hideyuki; Nakamura Masaya (Molecular Brain, 2013)
Abstract Background The transplantation of neural stem/progenitor cells (NS/PCs) at the sub-acute phase of spinal cord injury, but not at the chronic phase, can promote functional recovery. However, the reasons for this difference and whether it involves the survival and/or fate of grafted cells under these two conditions remain unclear. To address this question, NS/PC transplantation was performed after contusive spinal cord injury in adult mice at the sub-acute and chronic phases. Results Quantitative analyses using bio-imaging, which can noninvasively detect surviving grafted cells in living animals, revealed no significant difference in the survival rate of grafted cells between the sub-acute and chronic transplantation groups. Additionally, immunohistology revealed no significant difference in the differentiation phenotypes of grafted cells between the two groups. Microarray analysis revealed no significant differences in the expression of genes encoding inflammatory cytokines or growth factors, which affect the survival and/or fate of grafted cells, in the injured spinal cord between the sub-acute and chronic phases. By contrast, the distribution of chronically grafted NS/PCs was restricted compared to NS/PCs grafted at the sub-acute phase because a more prominent glial scar located around the lesion epicenter enclosed the grafted cells. Furthermore, microarray and histological analysis revealed that the infiltration of macrophages, especially M2 macrophages, which have anti-inflammatory role, was significantly higher at the sub-acute phase than the chronic phase. Ultimately, NS/PCs that were transplanted in the sub-acute phase, but not the chronic phase, promoted functional recovery compared with the vehicle control group. Conclusions The extent of glial scar formation and the characteristics of inflammation is the most remarkable difference in the injured spinal cord microenvironment between the sub-acute and chronic phases. To achieve functional recovery by NS/PC transplantation in cases at the chronic phase, modification of the microenvironment of the injured spinal cord focusing on glial scar formation and inflammatory phenotype should be considered.